2010
DOI: 10.1016/j.ajog.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperglycemia and Adverse Pregnancy Outcome (HAPO) study: paving the way for new diagnostic criteria for gestational diabetes mellitus

Abstract: The Hyperglycemia and Adverse Pregnancy Outcome (HAPO) Study was performed in response to the need for internationally agreed upon diagnostic criteria for gestational diabetes, based upon their predictive value for adverse pregnancy outcome. Increases in each of the three values on the 75 gram, 2-hour oral glucose tolerance test are associated with graded increases in the likelihood of pregnancy outcomes such as large for gestational age, cesarean section, fetal insulin levels and neonatal fat content. Based u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
249
1
10

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(268 citation statements)
references
References 11 publications
8
249
1
10
Order By: Relevance
“…While most of these studies were technically well performed, they reflect the inconsistency of strategies and thresholds for diagnosing GDM [11]. The IADPSG Consensus Panel recently revised its recommendations for the diagnosis of GDM, particularly based on the results of the HAPO (Hyperglycemia and Adverse Pregnancy Outcome) study, aiming to close the 'lack of international uniformity in the approach to ascertainment and diagnosis of GDM' [20,25]. Although OGTT screening is recommended for all pregnant women, the Consensus Panel stated that more cost-effective strategies that do not require an OGTT should be developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of these studies were technically well performed, they reflect the inconsistency of strategies and thresholds for diagnosing GDM [11]. The IADPSG Consensus Panel recently revised its recommendations for the diagnosis of GDM, particularly based on the results of the HAPO (Hyperglycemia and Adverse Pregnancy Outcome) study, aiming to close the 'lack of international uniformity in the approach to ascertainment and diagnosis of GDM' [20,25]. Although OGTT screening is recommended for all pregnant women, the Consensus Panel stated that more cost-effective strategies that do not require an OGTT should be developed.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for an overnight fast might be a limitation; however, FPG measurement has been suggested to have a better test accuracy as a random plasma glucose test with reproducible values throughout the entire pregnancy [11,27]. The HAPO study further estimated that FPG measurement identifies about 50% of all affected women without additional 1 and 2 h OGTT values [25]. This is comparable to our findings, where 40-65% of women with GDM were diagnosed by an FPG level of 5.1 mmol/l or above in both the validation and evaluation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…(10,11) The Hyperglycaemia and Adverse Pregnancy Outcomes (HAPO) Study demonstrated that the degree of maternal glucose abnormality correlated with the severity of adverse pregnancy outcomes. (12) Women with GDM are also at significantly higher risk (up to 40%) of developing type 2 diabetes later in life. (13)(14)(15) GDM can be detected in pregnancy using a blood test to screen for elevated blood glucose concentrations during the antenatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Given the physiological complexity of PE/E, a large, collaborative multisite study along the lines of the Hyperglycemia and Adverse Pregnancy Outcome (HAPO) study [68] would be ideally suited to answer this question. Such a study would ultimately result in consensus regarding a screening and diagnostic algorithm.…”
Section: Discussionmentioning
confidence: 99%